Integrating Economics, Entrepreneurship, Accounting, and Health Technology: A Conceptual Framework for Sustainable Healthcare Innovation in Nigeria - Fayokemi Oluwabusayo Olomola (World Journal of Entrepreneurial Development Studies, 2026)
Nigeria's health system remains acutely strained by persistent problems of underfinancing, wasteful utilization, and unequal access, even after decades of reform and investment. The rapid development in the field of health technology, entrepreneurship of enterprises, and rising demands for transparency and accountability in the expenditure of health money have mounted challenges as well as opportunities. This essay argues that productive innovation in Nigeria's health sector requires a multidisciplinary conceptual approach integrating economics, entrepreneurship, accounting, and health technology. Drawing from international and Nigerian literature, this essay explores intersections of the disciplines, highlighting the weakness of solo approaches and calling for multidisciplinary cooperation. The proposed model positions economics at the center of resource policy and planning, entrepreneurship as the innovation driver and scale, accounting as the guarantor of resilience and transparency, and health technology as the change driver. The paper provides strong opinions on integration needs, discredits opposing arguments on grounds of cost and complexity, and presents logical responses. Policy, practice, and education implications are identified, with recommendations for research, pilot testing, and training of staff. The paper concludes with the need for the dismantling of disciplinary silos and the adoption of a comprehensive approach towards the establishment of fair, effective, and sustainable healthcare innovation in Nigeria. This meeting of minds offers a framework for the stakeholders, policymakers, practitioners, educators, and entrepreneurs to collaborate in addressing Nigeria's health issues and tapping the maximum potential of innovation for the collective good.